Do stays abroad increase intercultural and general competences, affecting employability? - Petia Genkova; Lisa Kruse (Leadership, Education, Personality. An Interdisciplinary Journal, 2020)
With a globalized and growing world market, companies and educational institutions are getting more and more ambitious to re-orient their work patterns to the international level. Universities reacted to the demands of the globalized economy for flexibility and adaptability by the internationalization of their study programs. Research question: Do stays abroad and therefore intercultural experiences of students actually promote occupational competences and personal development? Design: In order to investigate this relationship, an online survey was employed, and a sample of N = 367 students, who had spent at least one semester abroad before, was recruited. The questions were aimed at measuring characteristics of the participants' stays abroad, as well as occupational engagement, resilience, intercultural competence personality characteristics related to job performance. Results: The findings suggest that experience abroad can partly enhance employability by serving as an additional job qualification. The results reveal that people who have experienced a stay abroad show higher work and study commitment and are more ambitious regarding their work. Furthermore, people with experience abroad show higher levels of resilience. They are more active concerning problem solving and have higher abilities to maintain emotional distance to work. Additionally, people show the more cultural intelligence the longer they stay abroad. Regarding the manifestation of cultural intelligence, the contact quality with the host country nationals played a significant role. It was evinced that higher contact quality is associated with higher values of cultural intelligence. Regarding occupational performance capacity, the results highlight that participants with a stay abroad are more dominant in an occupational context, i.e., they are more oriented towards superiority above others. Value: The present study contributes to the understanding of relevant personal skills and characteristics in intercultural contexts and of how personality might affect the process of becoming more competent. By demonstrating that stays abroad can increase certain work-related competences for students this study indicates that companies and educational institutions should spend more recourses on fostering experiences abroad of students and workers, in order to stay in tune with the requirements of globalization.
Keywords: 330; International mobility; Intercultural competence; Acculturation; Stay abroad; Competence